Green Production of Chitin from Black Soldier Fly Pupae Using a Natural Deep Eutectic Solvents - Nila Tanyela Berghuis; Raisya Salsabila; Shanny Fridarima; Ananda Azhari Aprianty Pabo; Intan Puspita Sari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Natural deep eutectic solvents (NADES) are eco-sustainable, non-toxic, non-volatile, renewable, reusable, and biodegradable, and are composed of natural compounds. NADES were developed as a new-generation solvent for extracting chitin from black soldier fly (BSF) pupae, and its effectiveness for demineralization and deproteinization was determined. Here, two promising NADES, consisting of mixtures of choline chloride-betaine-xylitol (NADES A) and choline chloride-malic acid-water (NADES B), were tested. Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to investigate the changes in the chemical composition of the extracted chitin. α-chitin revealed at wavenumbers 1660-1500 cm-1, in the amide group and decomposed at 330-350°C. NADES A and NADES B have a crystalline index of 91.65% and 90.65%, respectively. The chitin-NADES A and chitin-NADES B surfaces reveal the repetition of square, pentagonal, and hexagonal units (250× magnification) and fibrils (25,000× magnification). This study provides a green approach for chitin production from BSF and reveals the potential of NADES for extracting bio-polymers from natural sources.